Developing LKPD Based on Students' Learning Styles for Flat Shapes Material in Grade IV Mathematics in Elementary Schools - Ulya, Syarifatul; Afriyani, Dona (Journal of Islamic Education Students (JIES), 2024)
This research was motivated by problems found at SD IT Mesjid Raya Lantai Batu which showed low student learning outcomes due to the lack of variety in the teaching materials used by teachers. This research aims to produce LKPD based on students' learning styles that are valid and practical. This type of research is development research using 4D models (define, design, development, and desseminate). However, due to limited costs and time, this development research only reached the development stage. The instruments used were validity questionnaires, teacher response questionnaires, and student response questionnaires. Based on the research results, it shows that the LKPD based on student learning styles that has been designed is very valid with an average percentage of 90.17% and the results of the practicality of the teacher response questionnaire are very practical with an average percentage of 85.08%, while the results of the student response questionnaire are very practical with an average percentage of 86.02%. So that LKPD based on students' learning styles is suitable for use in the learning process.